Effects of Instrumentality and Personal Force on Deontological and Utilitarian Inclinations in Harm-Related Moral Dilemmas - Ludwig, Jonas; Reisenzein, Rainer; Hiemisch, Anette (Frontiers in Psychology, 2020)
Moral dilemmas often concern actions that involve causing harm to others in the attempt to prevent greater harm. But not all actions of this kind are equal in terms of their moral evaluation. In particular, a harm-causing preventive action is typically regarded as less acceptable if the harm is a means to achieve the goal of preventing greater harm than if it is a foreseen but unintended side-effect of the action. Likewise, a harm-causing preventive action is typically deemed less acceptable if it directly produces the harm than if it merely initiates a process that brings about the harmful consequence by its own dynamics. We report three experiments that investigated to which degree these two variables, the instrumentality of the harm (harm as means vs. side-effect; Experiments 1, 2, and 3) and personal force (personal vs. impersonal dilemmas; Experiments 2 and 3) influence deontological (harm-rejection) and utilitarian (outcome-maximization) inclinations that have been hypothesized to underly moral judgments in harm-related moral dilemmas. To measure these moral inclinations, the process dissociation procedure was used. The results suggest that the instrumentality of the harm and personal force affect both inclinations, but in opposite ways. Personal dilemmas and dilemmas characterized by harm as a means evoked higher deontological tendencies and lower utilitarian tendencies, than impersonal dilemmas and dilemmas where the harm was a side-effect. These distinct influences of the two dilemma conceptualization variables went undetected if the conventional measure of moral inclinations, the proportion of harm-accepting judgments, was analyzed. Furthermore, although deontological and utilitarian inclinations were found to be largely independent overall, there was some evidence that their correlation depended on the experimental conditions.